2018
DOI: 10.1002/lary.27167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postoperative steroids on post‐tonsillectomy pain and need for postoperative physician contact

Abstract: 4. Laryngoscope, 128:2187-2192, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…They concluded that steroids should be used with caution as they may increase the severity of bleeding episodes. Notably, this meta-analysis was published prior to that of Redmann et al, 25 who recently published a retrospective review of 1200 patients, 900 of whom received postoperative steroids. They found an overall hemorrhage rate of 7%, with a significant 4% decrease in the steroid groups.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that steroids should be used with caution as they may increase the severity of bleeding episodes. Notably, this meta-analysis was published prior to that of Redmann et al, 25 who recently published a retrospective review of 1200 patients, 900 of whom received postoperative steroids. They found an overall hemorrhage rate of 7%, with a significant 4% decrease in the steroid groups.…”
Section: Discussionmentioning
confidence: 99%
“…Since adoption of this standard at our institution, data supporting the efficacy of postoperative dexamethasone have led to inclusion of oral dexamethasone, though so far in a somewhat more limited capacity than that described by Redmann et al. 58 The rapidly evolving state of the art, as evidenced by the research highlighted in this review, call for periodic reassessment of practice patterns, and further adjustments will undoubtedly occur in the future.…”
Section: Our Approachmentioning
confidence: 93%
“…Positive clinical results from intravenous dexamethasone, combined with efforts to move away from opioids, has increased interest in a potential role for oral steroids in the postoperative period. A study by Redmann et al 58 examined the effect of adding dexamethasone (0.5 mg/kg, maximum dose 20 mg, every other day for 3 doses) to a regimen of scheduled acetaminophen and ibuprofen, along with rescue oxycodone for patients age 6 and over. They found a significant reduction in phone calls for pain and lower incidence of bleeding, and no incidents of steroid-related complications.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…170,171 They may also be utilized in sinonasal disorders and perioperative care. 172-175 Topical applications are frequently applied for adenoid, sleep, and sinonasal problems. 169,176-179 Some have considered holding SCSs during surgery for posttonsillectomy bleeding.…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…Corticosteroids are frequently indicated in children with airway compromise and laryngotracheal disorders 170,171 . They may also be utilized in sinonasal disorders and perioperative care 172‐175 . Topical applications are frequently applied for adenoid, sleep, and sinonasal problems 169,176‐179 .…”
Section: Pediatric Considerationsmentioning
confidence: 99%